Avoiding an unintentional space war: Lessons from Cold War nuclear diplomacy. (4th May 2021) - Simon, Maxwell; Wilson, Sam
ABSTRACT: The realm of outer space is becoming increasingly crowded and more contested – conditions that increase the risk that a conflict could arise. Given that there has never been a war in space, countries have little experience to draw upon to predict what behavior might motivate a potential competitor to respond with threatening actions – and how quickly and in what manner those actions could escalate to a full-blown conflict. To help control this situation, we may want to take a look at what was done during the Cold War, when concerns about unintentional escalation focused on nuclear weapons.